Assessment of drip and flood irrigation on biomass production, nutrient content and water use efficiency of maize (Zea mays L.) - Ali, AHMZ; Ahmed, SU; Rahman, MM; Rahman, MK (Dhaka University Journal of Biological Sciences, 2013)
An experiment was conducted in wooden boxes to assess flood, surface and sub-surface drip irrigation on biomass production, nutrient content and water use efficiency of maize (Zea mays L.). Four levels of irrigation treatments were applied: (i) SD1 = Drip irrigation pipe was set up on the surface of the soil ; (ii) SSD2 = Drip irrigation pipe was buried up to 5 cm depth; (iii) SSD3 = Drip irrigation pipe was buried up to 7.5 cm depth and (iv) FI = Flood irrigation was practiced without any drip irrigation pipe. Leaf area, leaf area index and biomass production of maize were significantly (p < 0.05) higher in SSD3 than SSD2 and FI treatments. Biomass production was 37.2, 41.1, 54.2 and 35.2 g in SD1, SSD2, SSD3 and FI treatments, respectively. Water use efficiency (WUE) was also significantly (p < 0.05) higher in surface and sub-surface drip irrigation than flood irrigation. Values for WUEs were 0.248, 0.298, 0.430 and 0.156 kg/m3 in SD1, SSD2, SSD3 and FI treatments, respectively. As a result, all three drip irrigation treatments enhanced water use efficiencies than flood irrigation. Comparing the three drip irrigation treatments, significantly (p < 0.05) higher nitrogen was found both in leaf and stem (3.3 and 3.8%) in sub-surface drip irrigation at 7.5 cm depth than flood irrigation (2.2 and 1.4%). Although, potassium contents in leaf and stem were not significantly different between the treatments, but had a tendency to be higher in drip irrigation treatments. Above all, drip irrigation performed better with higher water use efficiency. Dhaka Univ. J. Biol. Sci. 22(1): 47-54, 2013 (January)